Girls acting catty - Margolis, Leslie (Bloomsbury, 2009)
Sixth-grader Annabelle spends autumn coping with competing groups of friends at school, her mother's pre-wedding stress, learning to get along with a cute stepbrother-to-be, and such momentous events as wearing her first bra and learning to shave her legs.